PENGARUH TINGKAT PENDIDIKAN, KUALITAS PELATIHAN, DAN PENGALAMAN KERJA APARATUR DESA TERHADAP KUALITAS LAPORAN KEUANGAN DESA (STUDI KASUS PADA KECAMATAN AMARASI KABUPATEN KUPANG) - Fransiskus N. Naiola; Wilsna Rupilu; Agusta Amanda Wulandari; Tiffany N. P. Gah (JAKA - Jurnal Jurusan Akuntasi, 2020)
The purpose of this study was to determine the effect of education level, training quality, and workexperience of village officials on the quality of village financial report. The research method used isquantitative research methods. This research is a census research, where the population is all villageofficials who work in the village office in the District of Amarasi, Kupang Regency, and the sample usedis 40 respondents. The data used are primary data and data collection is done through a questionnaire.For the data analysis method using multiple linear regression. From the results of this study it can beconcluded that the level of education has no effect on the quality of village financial reports. Meanwhile,the quality of training and work experience have an effect on the quality of village financial reports. Thevariable that has the highest t-count value is the work experience variable. This means that the qualityof village financial reports is more driven by the work experience of each village apparatus. Thesuggestion that can be given from this research is that it is hoped that the Village Heads in AmarasiSubdistrict, Kupang Regency should pay more attention to the level of education, quality of training,and work experience because this will affect the quality of village financial reports.